ANALISIS FINANCIAL DISTRESS BANK UMUM MILIK NEGARA (BUMN) MASA PANDEMI COVID 19 - Herlin (Universitas Nusa Putra, 2021)
The purpose of this study was to analyze financial distress using the Altman (Z-Score) method at Bank Umum Milik Negara (BUMN) during pandemin Covid 19. The results showed that PT. BRI (Persero) Tbk with a condition that is not financial distress in years 2015 and 2016. In years 2017, 2018 and 2019 included in the gray area. PT. BNI 46 (Persero) Tbk in years 2015 meaning is not financial distress. Years 2016, 2017, 2018 and 2019 this means it is included in the gray area. PT. Bank Mandiri (Persero) Tbk, in year 2015, 2016, 2017, 2018 and 2019 it is included in a gray area. PT. BTN (Persero) Tbk in year 2015 included in the gray area, years 2016, 2017, 2018, 2019 this shows that PT. BTN (Persero) Tbk expriencing financial distress